Dexamethasone Use During Pregnancy: Potential Adverse Effects on Embryonic Skeletogenesis - Cheng, Xin; Wang, Guang; Ka Ho Lee, Kenneth; Yang, Xuesong (Current Pharmaceutical Design, 2014)
Glucocorticoids are important regulators of cell differentiation and mesenchymal cell lineage commitment during skeletogenesis. In clinical practice, it has been difficult to study the effects of glucocorticoids on target tissues because patients taking glucocorticoids often suffer from adverse skeletal effects. Dexamethasone (Dex) is a long-acting synthetic corticosteroid hormone that ranks amongst the most widely used prescribed drugs, and it is a powerful medication that is increasingly employed during the perinatal and neonatal periods. However, Dex is a potential teratogen. In particular, it has been claimed that Dex exposure during pregnancy can affect osteogenesis in the developing embryo, although this claim remains highly controversial. In this review, we summarize the published data from numerous clinical follow-up, animal-based and in vitro studies on the effects of Dex exposure on embryonic skeletogenesis. These studies indicate that Dex may adversely affect skeletal progenitor cells during development. In addition, Dex can exert a number of effects on bone growth at different developmental stages. We also discuss how glucocorticoids influence the BMP, FGF, Hedgehog and Wnt signaling pathways, which are key regulators of skeletogenesis in the embryo. A fuller understanding of the negative, and perhaps teratogenic, effects of Dex on skeletogenesis will have important implications for the routine use of Dex in clinical practice.
Keywords: dexamethasone (Dex)